Completeness of cause of injury coding in healthcare administrative databases in the United States, 2001. Issue 3 (2nd June 2006) - Coben, J H; Steiner, C A; Barrett, M; Merrill, C T; Adamson, D
Abstract : Objectives: To determine the completeness of external cause of injury coding (E-coding) within healthcare administrative databases in the United States and to identify factors that contribute to variations in E-code reporting across states. Design: Cross sectional analysis of the 2001 Healthcare Cost and Utilization Project (HCUP), including 33 State Inpatient Databases (SID), a Nationwide Inpatient Sample (NIS), and nine State Emergency Department Databases (SEDD). To assess state reporting practices, structured telephone interviews were conducted with the data organizations that participate in HCUP. Results: The percent of injury records with an injury E-code was 86% in HCUP's nationally representative database, the NIS. For the 33 states represented in the SID, completeness averaged 87%, with more than half of the states reporting E-codes on at least 90% of injuries. In the nine states also represented in the SEDD, completeness averaged 93%. Twenty two states had mandates for E-code reporting, but only eight had provisions for enforcing the mandates. These eight states had the highest rates of E-code completeness. Conclusions: E-code reporting in administrative databases is relatively complete, but there is significant variation in completeness across the states. States with mandates for the collection of E-codes and with a mechanism to enforce those mandates had the highest rates of E-code reporting. Nine statewide ED data systems demonstrate consistently high E-coding completeness.